Evaluation of different nitrogen sources on growth and fermentation performance for enhancing ethanol production by wine yeasts - Rojo, Cecilia; Talia, Paola Mónica; Lerena, María Cecilia; Ponsone, María Lorena; Gonzalez, Magali Lucia Rosa; Becerra, Lucia Maribel; Mercado, Laura Analia; Martín-Arranz, Virginia; Rodriguez Gomez, Francisco; Arroyo Lopez, Francisco Noe; Combina, Mariana (Elsevier, 2023)
The utilization of grape juice from low oenological value grape varieties for bioethanol production represent an alternative for diversification and value addition in viticulture. Optimizing Very High Gravity (VHG) fermentation can significantly increase ethanol productivity while reducing water and energy consumption. In this study, the impact of different nitrogen sources on growth and fermentative performance of locally selected yeast strains was investigated. Five yeast strains of species Saccharomyces cerevisiae and Zygosaccharomyces rouxii were cultured in both synthetic culture media and natural grape juice supplemented with ammonium sulfate (NH), yeast extract (YE), Fermaid K (FERM), and urea (U) at varying concentrations. Due to the very low fermentation rate, the Z. rouxii strain was excluded from the selection. The results obtained in synthetic medium showed that nitrogen sources that promoted growth (NH and YE) had minimal effects on fermentative performance and were highly dependent on the specific yeast strain. However, the combination of urea and ammonium favored the rate of sugar consumption. When validated in natural grape juice, urea combined with ammonium (U + NH 300 + 75 mg/L) improved both growth parameters and ethanol yield. Doubling the concentration (U + NH 600 + 150 mg/L) further enhanced sugar consumption and ethanol production while reducing unwanted by-products. The combined use of urea and ammonium exhibited a synergistic effect, making it a cost-effective nitrogen supplement for VHG fermentations.